Evolution of Natural Transformation: Testing the DNA Repair Hypothesis in Bacillus Subtilis and Haemophilus Influenzae - Redfield, R. J. (1993)
The hypothesis that the primary function of bacterial transformation is DNA repair was tested in the naturally transformable bacteria Bacillus subtilis and Haemophilus influenzae by determining whether competence for transformation is regulated by DNA damage. Accordingly, DNA damage was induced by mitomycin C and by ultraviolet radiation at doses that efficiently induced a known damage-inducible gene fusion, and the ability of the damaged cultures to transform was monitored. Experiments were carried out both under conditions where cells do not normally become competent and under competence-inducing conditions. No induction or enhancement of competence by damage was seen in either organism. These experiments strongly suggest that the regulation of competence does not involve a response to DNA damage, and thus that explanations other than DNA repair must be sought for the evolutionary functions of natural transformation systems.